The Impact of bank-specific and macroeconomic variables on the profitability of banks from selected African countries (International Journal of Scientific Research and Management (IJSRM), 2022)
This was an empirical investigation of the impact of bank-specific and macroeconomic variables on the profitability of banks in selected countries in Africa, over the period 2009 to 2019. The study focused on 33 banks operating across 9 African countries, namely South Africa, Uganda, Kenya, Tunisia, Egypt, Namibia, Zambia, Nigeria and Ghana, as representative of the continent. The analyses of the various interrelations were done using the dynamic panel data modelling approach. The study used an unbalanced panel of commercial banks’ data in the selected countries to estimate the model with both the return on equity and the return on assets as proxies for profitability. Of the bank-specific variables, net interest margin, loan loss and cost to income ratios have a statistically significant negative relationship with profitability. The relationship between non-performing loans, capital adequacy and profitability is statistically not significant. There is however, a positive and statistically significant relationship between profitability and macroeconomic-specific variables. Overall the study shows mixed impacts of bank-specific and macroeconomic variables on the profitability of banks in the selected countries in Africa, although they are at a different level of regulatory and supervisory regimes, including the pace of technological developments and implementation.